The Association between Hypertension and the Incidence of Type 2 Diabetes Mellitus in Semarang City in 2010-2015 - Hadi Kurniawan; Sri Ratna Rahayu; Dina Nur Anggraini Ningrum (Public Health Perspective Journal, 2026)
One of the most common causes of mortality related to noncommunicable disease is diabetes mellitus. Driven by the high number of people living with diabetes globally, Indonesia ranks fifth with approximately 19.5 million diabetes cases (IDF, 2021).  The nation that is Indonesia's provides the latest statistic that shows the prevalence of diabetes has been increasing over the five-year stretch of 1.5% in 2018 to 1.7% in 2023 for all ages, and for those 15 years and older is 2.0% in 2018 to 2.2% in 2023. Among the 38 provinces of Indonesia, Central Java ranks 8 in for diabetes. In the last calendar year with reports ranging from 2022 to 2023, Semarang City reported a 2.08% increase and the Module 1a (2 diabetes 0% target) has shown no shifts and zero diabetes and obesity (0%) target has been shown. At the same time, many people suffering from type 2 diabetes mellitus continue to suffer from hypertension. This research is going to discuss the epidemiological trends of T2DM and hypertension to understand the link between hypertension and T2DM based on gender and age. This is a quantitative and observational study based on the research of the Semarang City SIMPUS system of the years 2010 to 2015 and analyzed using the univariate method (using frequency distribution) and the bivariate method (using chi-square test). Findings indicate an alarming trend of higher prevalence of comorbid diabetes type 2 and hypertension among women than men.